Vulvodynia and chronic pelvic pain in a gynecologic outpatient clinic - Gerda Trutnovsky; Christina Plieseis; Vesna Bjelic-Radisic; Marie-Christine BertholinyGalvez; Karl Tamussino; Daniela Ulrich (Taylor & Francis Group, 2019)
Introduction: Vulvodynia and chronic pelvic pain are common but underdiagnosed chronic gynecologic pain syndromes. Insufficient knowledge regarding prevalence, typical pain patterns and associated factors contribute to delayed diagnosis. The present study explored the symptoms and characteristics of women presenting with vulvodynia and/or chronic pelvic pain to a gynecologic outpatient clinic. Materials and methods: Electronic charts of women diagnosed with vulvodynia and/or chronic pelvic pain between January 2010 and December 2015 were reviewed. Type of pain, duration of symptoms, previous medical assessments and therapies, comorbidities and patient characteristics were analyzed with descriptive statistics. Results: One hundred and twenty-seven women (mean age 36, range 18-75 years) met the diagnostic criteria for chronic gynecologic pain syndromes. Sixty-five women were diagnosed with CPP only, 42 with vulvodynia and 20 with both conditions. Endometriosis was suspected or diagnosed in 35 (54%) women with CPP. History of pain ranged from 3 months to 20 years. Comorbidities were common, with 40% of women being diagnosed with depression or other mood disorders, 15% with urological and 9% with gastrointestinal conditions. Conclusions: There is a need for increased awareness regarding vulvodynia and CPP among health care providers. A comprehensive history is important for adequate diagnosis.